Previous hypertensive hemorrhage increases the risk for bleeding and ischemia for PCI patients on dual antiplatelet therapy. (3rd June 2017) - Qiao, Manli; Bi, Qi; Fu, Paul; Wang, Yixin; Song, Zhe; Guo, Fang
Abstract: Objectives : The use of antiplatelet therapy after intracerebral hemorrhage remains controversial, while the use of dual antiplatelet therapy (DAPT) is required after cardiac stenting. In this study, we examine the risk of bleeding and ischemic events for PCI patients with a history of hypertensive hemorrhage on DAPT. Methods: A total of 128 cases and 153 controls were selected from Chinese patients with cardiac stenting on dual anti-platelet therapy for a single-center retrospective case-control study. Patients with a history of hypertensive hemorrhage were selected for the case group, while patients with a history of hypertension were chosen as control. All patients were on aspirin 100 mg and clopidogrel 75 mg after cardiac stenting, and were followed for a duration of 12–48 months. The primary outcomes were intracerebral hemorrhage, major bleeding, and major adverse cardiovascular and cerebrovascular events. Results: A history of previous hypertensive hemorrhage was not found to be a risk factor for intracerebral hemorrhage and major bleeding while on dual anti-platelet therapy. However, a history of either hypertensive hemorrhage or coronary artery disease was independently found to be risk factors for major adverse cardiovascular and cerebrovascular events. On sub-group analysis, patients with a history of hypertensive hemorrhage within 12 months were found to be at higher risk for bleeding on dual anti-platelet therapy, while patients with history of hypertensive hemorrhage outside of 12 months on dual anti-platelet therapy did not have the same increased risk. Conclusion: A history of hypertensive hemorrhage and coronary heart disease were two independent risk factors for major adverse cardiovascular and cerebrovascular events in PCI patients taking DAPT. A history of hypertensive hemorrhage less than 12 months had an increased risk for recurrent intracerebral hemorrhage and major bleeding in PCI patients taking DAPT.